ChatGPT as a Universal Design for Learning Tool : Supporting College Students with Disabilities - Ayala, Sandra (Educational (Re)naissance, 2024)
This paper explores the potential of ChatGPT, an innovative AI language model, as an assistive technology tool within the framework of Universal Design for Learning (UDL) to provide targeted support for college students with disabilities. As colleges and universities strive to promote inclusive practices, the implementation of UDL principles has gained significance. ChatGPT's interactive conversational interface aligns seamlessly with UDL, offering personalized assistance, promoting comprehension, and creating engagement opportunities among diverse learners. Numerous examples are provided, which align with both the universal design framework and the needs of learners receiving accessible and assistive services on a college campus. This paper identifies the many possibilities for ChatGPT as an accommodation tool to significantly impact and improve the inclusive and equitable learning experiences of college students with disabilities.